SW산업 종사자들의 개인적 특성이 직무만족도에 미치는 영향 - 내재적 보상과 외재적 보상 조절효과 - 김효정; Kim, Hyojung ((사)디지털산업정보학회 논문지, 14(2), 2018)
This study analyzed the personal characteristics of the SW industry workers and investigated how these individual characteristics affect the satisfaction of job satisfaction. In addition, we examined how satisfaction with these jobs varies according to satisfaction with internal control and external compensation. This study surveyed the employees of SW industry in Seoul and Daegu from September 15 to October 15, 2017. The results of this study are as follows. First, personal characteristics have a significant effect on job satisfaction. Second, extroversion, openness, friendliness and integrity have a significant effect on job satisfaction. This is consistent with the previous study (Park and Song, 2005), which suggests that people with extroversion are more likely to feel positive emotions such as joy. In addition, it is believed that open empathy has a tendency to share with others in work, and positive emotions in work have a significant influence because they show high achievement in work. A friendly person places great importance on a comfortable and harmonious relationship with others, so he builds and maintains good relationships with the members of the organization by trusting others in the organization. Third, nervousness showed no significant effect on job satisfaction. This is consistent with the previous study (Yoo, 1987) in which the more nervousness is, the more unpleasant emotions work and the more negative emotions and negative experiences occur. Fourth, personal characteristics have positive effects on job satisfaction in the moderating effects of intrinsic compensation and external compensation. There is a difference in job satisfaction due to intrinsic compensation and external compensation.